Biomarkers Identifying Tendency to Suicide (BITS): detection of biomarkers in adolescents with suicidal ideation or suicidal behavior for early prevention or intervention. A prospective cohort study - Orlandi, Marika; Marazzi, Francesca; Morandi, Chiara; Gastaldi, Matteo; Borgatti, Renato; Mensi, Martina Maria (Frontiers in Human Neuroscience, 2026)
Adolescent suicidality represents a major and persistent public health concern, with sustained increases in suicidal ideation and behaviors observed in recent years. Although suicide risk is widely conceptualized as a complex and multifactorial phenomenon, biological vulnerability factors remain insufficiently integrated into adolescent clinical assessment frameworks. In particular, neuroinflammatory processes, hypothalamic–pituitary–adrenal (HPA) axis dysregulation, and alterations in blood-brain barrier integrity have emerged as potentially relevant but underexplored contributors to suicidality. This prospective clinical cohort study adopts an integrative, multi-method approach to enhance the characterization of suicidality among help-seeking adolescents. We hypothesize that adolescents with suicidal ideation or suicidal behaviors will show distinct peripheral biomarker profiles compared with adolescents without suicidal concerns. The primary analyses focus on group differences at baseline in inflammatory cytokines, markers of systemic inflammation, HPA-axis activity, and blood-brain barrier-related biomarkers, as well as measures of suicidality severity and global functioning. Secondary outcomes include associations between biomarker levels and psychopathological severity and functioning, and longitudinal changes in biological and clinical measures, including transitions in suicidality status, over a 2-month follow-up. Participants will undergo a comprehensive psychodiagnostic assessment and standardized peripheral blood sampling at baseline and follow-up. By integrating biological measures with detailed psychological and behavioral profiling within a longitudinal design, this protocol aims to establish a framework for biomarker-informed risk stratification of high-risk adolescents, ultimately informing more precise and developmentally sensitive suicide prevention strategies.